Informed consent in provision of sexual and reproductive health services - Benavides, Alfredo (2015)
Background. Informed consent appears in the modern world as an instrument for autonomy principle observation imposed by bioethics. It signifies a change in medical profession practice that replaces the paternalist model based on beneficence for persons’ liberty to decide on diagnostic or therapeutic intervention and in biomedical research. Informed consent is mandatory. As established by bioethics principles and Lex Artis and founded in respect for human rights and laws. Its inobservance is sanctioned. Informed consent in sexual and reproductive health. In human sexuality and reproduction it constitutes fundamental element recognized in the field of specific norms of most clinical and research applications. Previous information. To consent is to take position on something chosen without obligation or coerced. Enough information is required during doctor-patient relation, where the latest whether accepts or not to be subjected to diagnostic of therapeutic procedure, or to research. Written form consent certifies that a person has received and comprehended information given by the physician or other health professional for a determinate procedure. Conclusions. Informed consent is an ethical and legal requirement prior to any diagnostic or therapeutic intervention in sexual and reproductive health.